School-Based Disaster Psychoeducation to Improve Student Preparedness in Hydrometeorological Disasters: Psikoedukasi Kebencanaan Berbasis Sekolah untuk Meningkatkan Kesiapsiagaan Siswa Menghadapi Bencana Hidrometeorologi - Sari, Reza Lidia; Herdiana, Ike; Lakoro, Rahmatsyam (Universitas Lancang Kuning, 2025)
Indonesia's geographical location makes it a potential country to experience natural disasters. As a vulnerable group, children need to receive information on preparedness for natural disasters. Therefore, the community service team designed and implemented the